PERLINDUNGAN HUKUM BAGI PELAKU USAHA TRANSPORTASI ONLINE DALAM INDUSTRI 4.0 - Muhamad Arif Fahmi; Ahmad Munir; Ainul Masruroh (universitas islam darul ulum lamongan, 2019)
In Indonesia, the last five years is very rapid development of technology until it penetrated into the field of transportation called online transportation. The existence of online transportation is hypothesized by most people as a positive part of the evolution of Industry 4.0 in the field of transportation in Indonesia. Not a few people also look negatively at this online transportation, because the existence of online transportation is considered to displace the existence of conventional transportation and the impact of income from conventional transportation is decreasing. The need for legal protection against online transportation businesses and conventional transportation must be provided by the government. This research is a normative research that examines regulations related to transportation and legal protection of online transportation businesses. Then there needs to be a role from the government to provide a legal umbrella on this online transportation.